2010
DOI: 10.1590/s0102-86502010000100015
|View full text |Cite
|
Sign up to set email alerts
|

The influence of methylene blue on the healing of intestinal anastomoses subjected to ischemia and reperfusion in rats

Abstract: PURPOSE: To investigate the influence of methylene blue, on the healing of intestinal anastomoses subjected to ischemia and reperfusion in rats. METHODS: Forty-five rats divided into the following three groups were used: control (G1); ischemia without methylene blue (G2); and ischemia with methylene blue (G3). A laparotomy was performed and the cranial mesenteric artery isolated. Whereas the cranial artery was temporarily occluded for 45 minutes in groups G2 and G3, prior to enterotomy and intestinal anastomos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…For the same reason this molecule was chosen in other experiments [23][24][25][26] and in the present study. On the other side, the study of Miranda et al 27 demonstrated that MB infusion had not beneficial effect on the healing of intestinal anastomoses in an experimental I/R model in rats.…”
Section: Discussionmentioning
confidence: 97%
“…For the same reason this molecule was chosen in other experiments [23][24][25][26] and in the present study. On the other side, the study of Miranda et al 27 demonstrated that MB infusion had not beneficial effect on the healing of intestinal anastomoses in an experimental I/R model in rats.…”
Section: Discussionmentioning
confidence: 97%